Prevention and Clinical Management of Periodontal Health in Pregnancy - Depi Praharani; Melok Aris Wahyukundari; Neira Najatus Sakinah; Desi Sandra Sari; Peni Pujiastuti; Yuliana Mahdiyah Da'at Arina (KHD Production, 2026)
Pregnancy induces significant hormonal and immunological changes that increase susceptibility to gingival inflammation and may exacerbate existing periodontal conditions. Emerging evidence also suggests a potential association between periodontal disease and adverse pregnancy outcomes, including preterm birth and low birth weight. This review aims to synthesize current evidence on the pathophysiology of periodontal disease during pregnancy, its potential link to adverse pregnancy outcomes, and approaches to prevention and clinical management. A comprehensive literature search was conducted using PubMed, Scopus, and ScienceDirect for studies published between 2014 and 2025. The search strategy incorporated terms related to pregnancy, periodontal disease, periodontal therapy, and adverse pregnancy outcomes. Eligible studies included systematic reviews, meta-analyses, randomized controlled trials, and high-quality cohort studies published in English. Physiological increases in estrogen and progesterone during pregnancy enhance vascular permeability and modulate immune responses, thereby amplifying gingival inflammation even in the presence of minimal plaque accumulation. Furthermore, the translocation of periodontal pathogens and pro-inflammatory mediators—such as interleukin-1β (IL-1β), tumor necrosis factor-alpha (TNF-α), and prostaglandin E2 (PGE2)—into the systemic circulation and placental tissues provides biological plausibility for adverse pregnancy outcomes. Non-surgical periodontal therapy, particularly scaling and root planing (SRP), has been shown to improve maternal periodontal health and is considered safe, especially during the second trimester. However, its impact on pregnancy outcomes remains inconclusive due to heterogeneity among studies. Preventive strategies, including oral hygiene promotion and routine periodontal care, are consistently supported as effective and essential. Although a definitive causal relationship between periodontal disease and adverse pregnancy outcomes has not been established, maintaining periodontal health during pregnancy represents a safe and evidence-based component of comprehensive prenatal care. Future well-designed studies are needed to determine the optimal timing of interventions and the long-term maternal and fetal benefits.